Associated factors leading to exchange blood transfusion among severe neonatal jaundice in Kelantan 2015-2017 - Hanafi, Wan Soliha Wan Mohd (2018)
Background: Neonatal jaundice is a common disorder during the neonatal period. Jaundice may lead to worsening condition if it is not well monitored which steer up to severe jaundice level. Long-term results of severe neonatal jaundice may lead to devastating neurologic sequelae, including bilirubin encephalopathy and kernicterus. Exchange blood transfusion (ET) has remained the most effective and expeditious modality to rapidly lowering serum bilirubin concentration. Objective: This study aims to determine the proportion and factors associated with exchange blood transfusion procedure among severe jaundice neonates in Kelantan from 2015 to 2017. Methodology: This study applied the cross-sectional design on severe jaundice neonates in Kelantan between January 2015 and December 2017 using secondary data from Monitoring and Management Neonatal/ Neonatal Jaundice Forms from Maternal and Child Health unit, Kelantan Health State Department. Data obtained from sources including Microsoft Excel files and scanned hardcopy forms. Result: Out of 228 neonates who were admitted for severe jaundice, 45 neonates (17%) required ET procedure. The proportion of severe neonatal jaundice underwent ET are increasing in trend by 2015 to 2017 with 17.0%, 16.3% and 23.7% respectively. The significant associated factors to ET were infection of neonates (Adjusted Odd Ratio